Differences in blood pressure and vascular responses associated with ambient fine particulate matter exposures measured at the personal versus community level. Issue 3 (8th October 2010) - Brook, Robert D; Bard, Robert L; Burnett, Richard T; Shin, Hwashin H; Vette, Alan; Croghan, Carry; Phillips, Michael; Rodes, Charles; Thornburg, Jonathan; Williams, Ron
Abstract : Background: Higher ambient fine particulate matter (PM2.5 ) levels can be associated with increased blood pressure and vascular dysfunction. Objectives: To determine the differential effects on blood pressure and vascular function of daily changes in community ambient- versus personal-level PM2.5 measurements. Methods: Cardiovascular outcomes included vascular tone and function and blood pressure measured in 65 non-smoking subjects. PM2.5 exposure metrics included 24 h integrated personal- (by vest monitors) and community-based ambient levels measured for up to 5 consecutive days (357 observations). Associations between community- and personal-level PM2.5 exposures with alterations in cardiovascular outcomes were assessed by linear mixed models. Results: Mean daily personal and community measures of PM2.5 were 21.9±24.8 and 15.4±7.5 μg/m 3, respectively. Community PM2.5 levels were not associated with cardiovascular outcomes. However, a 10 μg/m 3 increase in total personal-level PM2.5 exposure (TPE) was associated with systolic blood pressure elevation (+1.41 mm Hg; lag day 1, p<0.001) and trends towards vasoconstriction in subsets of individuals (0.08 mm; lag day 2 among subjects with low secondhand smoke exposure, p=0.07). TPE and secondhand smoke were associated with elevated systolic blood pressure on lag day 1. Flow-mediated dilatation was not associated with any exposure. Conclusions: Exposure to higher personal-level PM2.5 during routine daily activity measured with low-bias and minimally-confounded personal monitors was associated with modest increases in systolic blood pressure and trends towards arterial vasoconstriction. Comparable elevations in community PM2.5 levels were not related to these outcomes, suggesting that specific components within personal and background ambient PM2.5 may elicit differing cardiovascular responses.